If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 30 = 120 Reorder the terms: 30 + 10x = 120 Solving 30 + 10x = 120 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 10x = 120 + -30 Combine like terms: 30 + -30 = 0 0 + 10x = 120 + -30 10x = 120 + -30 Combine like terms: 120 + -30 = 90 10x = 90 Divide each side by '10'. x = 9 Simplifying x = 9
| 12x-36+10x=15x+36-3x | | 8x+15y=-24 | | 4(x+3)=x(3-k) | | x+7=5(4x-3) | | abs(2x+5)=6x+23 | | 0=-0.4x^2+16x+90 | | 3(2H-14)=4(H-5) | | 8S+6=-18 | | 2(A+6)=10 | | 3E-4=E+16 | | 8-T=56+11T | | 6X+6=7X+9 | | 10-3I=-17 | | 5K-2=2K+10 | | 5(2D+1)=35 | | ln(128)-7ln(2)= | | log(128)-7log(2)= | | 2-7x+5=13-3x | | ln(2x)-ln(4x)= | | ax-b=bx-a | | 3y^2+8y-3=0 | | 4k+11=36 | | 1250g= | | -2x+15=30-0.5x | | 0.5x=2x-45 | | x=30-0.5x | | 3(2s-3)=-(7-s) | | f-8-3f=3-7+4 | | 4x-1.2=x | | -3x+4=6-x | | 53b+43y= | | 3x+4=6-x |